2019
DOI: 10.35940/ijeat.e1045.0785s319
|View full text |Cite
|
Sign up to set email alerts
|

Applying Machine Learning Techniques to Predict the Maintainability of Open-Source Software

Abstract: Software maintainability is a vital quality aspect as per ISO standards. This has been a concern since decades and even today, it is of top priority. At present, majority of the software applications, particularly open source software are being developed using Object-Oriented methodologies. Researchers in the earlier past have used statistical techniques on metric data extracted from software to evaluate maintainability. Recently, machine learning models and algorithms are also being used in a majority of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…with the agile methodologies and its implementation in software engineering projects, which they reduced with the help of AI based machine learning simulator of MATLAB. In 2019, Gopal and Amirthavalli [37] performed an empirical analysis on case study of open-source software, with an objective to predict relationship between maintainability and metrics, and observed that Instability metric is most influencing amongst all. In 2019, Kumar and Singh proposed [38] a threshold based segmentation using MATLAB tool to automate performance evaluation of students and evaluated that ML based procedure performs more accurately.…”
Section: Empirical Discussionmentioning
confidence: 99%
“…with the agile methodologies and its implementation in software engineering projects, which they reduced with the help of AI based machine learning simulator of MATLAB. In 2019, Gopal and Amirthavalli [37] performed an empirical analysis on case study of open-source software, with an objective to predict relationship between maintainability and metrics, and observed that Instability metric is most influencing amongst all. In 2019, Kumar and Singh proposed [38] a threshold based segmentation using MATLAB tool to automate performance evaluation of students and evaluated that ML based procedure performs more accurately.…”
Section: Empirical Discussionmentioning
confidence: 99%
“…Several machine learning algorithms are being used today due to the benefits they offer like prediction, analysis and model building etc… Madhwaraj & Amirthavalli [3] used machine learning techniques to predict the maintainability of open source software. Viswanath et al [4] performed a case study to predict the number of deaths due to dengue disease.…”
Section: Literature Reviewmentioning
confidence: 99%
“…LITERATURE REVIEW Today, a few machine learning algorithms are employed because of the advantages they provide, including prediction, analysis, model development, etc. Machine learning approaches were utilized by Madhwaraj & Amirthavalli [3] to forecast the maintainability of free software. To estimate the number of deaths brought on by dengue fever, Viswanath et al [1] conducted a case study.…”
Section: IImentioning
confidence: 99%